Tribological behaviour of shape memory alloys - Pua, Si Ying (2013)
This project aims to investigate the influencing factors on the coefficient of friction, and hence the ability to resist wear, of NiTi shape memory alloys. An extensive study of the effect of NiTi alloys in the martensitic phase in comparison with NiTi alloys in the austenitic phase, NiTi alloys in comparison with stainless steel and austenitic NiTi alloys using different counter-bodies, under different loading conditions were carried out. The phase transformation temperatures were measured by differential scanning calorimetry and the wear tests were conducted using a CETR tribometer at room temperature.